1983
DOI: 10.1111/j.1365-2605.1983.tb00326.x
|View full text |Cite
|
Sign up to set email alerts
|

Early effects of efferent ductule ligation on the proximal segment of the rat epididymis

Abstract: The effects on the proximal caput epididymidis of efferent ductule ligation were studied. After 6 h there was a slight increase in autophagocytosis in the initial segment proper (1A). After 12 h this segment showed cell death and cytoplasmic regression and after 24 h large amounts of necrotic cells and focal degeneration in the epithelium, and desquamated cells and débris in the lumen. After 48 h the epithelium was lower, but degeneration less obvious. Segments 1B, 1C and 2 showed marked cell death and cytopla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
22
1
1

Year Published

1992
1992
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 20 publications
5
22
1
1
Order By: Relevance
“…The relative lack of lysosomes in the cytoplasm of nonciliated cells in the blind-ending tubules may be due to a decrease or absence of rete testis fluid in these tubules. Nicander et al (1983) observed that rat efferent ductules deprived of rete testis fluid for 7 days had an empty, contracted lumen, a slightly increased epithelial height, and a more densely stained cytoplasm. However, the effect of fluid deprivation on the PASpositive granules was not reported.…”
Section: Discussionmentioning
confidence: 96%
“…The relative lack of lysosomes in the cytoplasm of nonciliated cells in the blind-ending tubules may be due to a decrease or absence of rete testis fluid in these tubules. Nicander et al (1983) observed that rat efferent ductules deprived of rete testis fluid for 7 days had an empty, contracted lumen, a slightly increased epithelial height, and a more densely stained cytoplasm. However, the effect of fluid deprivation on the PASpositive granules was not reported.…”
Section: Discussionmentioning
confidence: 96%
“…It has been well established that the epididymis, in particular the initial segment, is dependent on the testicular input of factors, other than androgens, directly to the epididymal lumen (Robaire et al 1981, Nicander et al 1983, Turner & Riley 1999; depriving the epididymis of these testicular factors (i.e. via efferent duct ligation) has well-documented effects on gene expression in the initial segment (reviewed in Hinton et al 1998).…”
Section: Growth Factor Systems In the Epididymismentioning
confidence: 99%
“…To verify the causal relationship of epididymal defects to a relative obstruction of epididymal ducts and the dilation and liquid accumulation of the upstream rete testis, we performed a bilateral efferent ductile ligation (ELG) (Nicander et al, 1983) and bilateral vasoligation (VLG) (Preslock et al, 1985) in Gpr48 wild-type mice at 3 weeks of age. At 12 weeks of age, the seminiferous epithelium in mice with either ELG or VLG demonstrated similar changes to those in Gpr48 -/-adult males (Fig.…”
Section: Malformation Of the Reproductive Tract And Infertility In Gpmentioning
confidence: 99%